Uptake ICT: a network of Stakeholder's against digital illiteracy - de Barros Dias, Isabel Maria (2018)
#Uptake_ICT2life-cycle: digital literacy and inclusion to learners with disadvantaged background# is an Erasmus + project that aims at enhancing digital literacy among adults with disadvantaged backgrounds. The partners have produced didactic materials and pedagogical guidelines to meet this aim. Based on these materials, and their didactical exploitation, a network of stakeholders was formed and trained in order to subsequently be able to teach citizens that both have disadvantaged backgrounds and are digitally illiterate or quasi-illiterate. This paper relates how this experience was undertaken in Portugal in what concerns the creation of the Stakeholders' network and presents its results.